Legal options for a green golden rule in the European Union's fiscal framework - Zsolt M. Darvas (Bruegel, 2022)
Achieving the European Union's climate goals and decoupling from Russian energy will require a massive increase in green public spending, which will be difficult when EU fiscal rules requiring fiscal consolidation are reinstated. The two major proposals to address the conflicting goals of fiscal consolidation and increased green public investment needs are a possible new European climate investment fund and a green golden rule. The latter would exclude any increase in net green public investment from the fiscal indicators used to measure compliance with fiscal rules, for countries with sound public finances. An EU climate fund and a well-designed green golden rule would be equivalent in terms of project selection, implementation and control procedures. If the climate fund does not involve redistribution across member states, then the treatment of related spending and consequent borrowing in national fiscal indicators and in the EU's fiscal framework would be the same. New regulations would be needed to set up both the climate fund and the green golden rule. Special legislation would be needed to exempt the subsequent climate expenditures from EU fiscal rules in both cases. A climate fund financed by EU borrowing with redistributive effects across countries would likely result in the exclusion of the fund's activities from national fiscal indicators and EU fiscal rules without any legislative changes. There are question marks about the desirability and political feasibility of redistribution across the EU for climate purposes. An EU climate fund, irrespective of whether or not it involves redistribution, would mainly benefit southern and eastern EU countries. An instrument is needed to foster green public investment in western and northern EU countries as well. The green golden rule would be such an instrument. While there are some pragmatic options to mimic a green golden rule in the current EU fiscal framework, such as amending the so-called 'investment clause' and adjusting the medium-term objective for the structural balance, ultimately, elements of the 2011 Six-Pack legislation and the 2012 Treaty on Stability, Coordination and Governance should be revised to include a green golden rule.
Keywords: 330; fiscal policy; european monetary union